(Effects of Chitosan-formic Addition on Retanning Process of Leather and Printing For Some Textiles Materials) - Rizal Alamsyah; Solechan -; Karyati Sugesti; Mohamad sidik (Balai Besar Industri Agro, 2003)
This study was designed to analyze the effects of chitosa-formic addtition to retanning of leather and printing proces of textile .the type of leather used was boks leather and those for textile consist of polyester,polyacrylic,contton, and nylon. chitosan was extracted from shrimps and crab shells which produced from shrimp shells, crab shells,and mixture from those shell was then mixed with formic acid(3%) to produce chitosan-formic with the concentration of 7.5% for each treatment.in retaning leather ,chitosan-formic was used as filling agents meanwhile in printing textiles these was applied for the low quality leather and itsesults was compared with the leather without chitosan-formic addition in textiles printing chitosan-formic was printed with any kids dyestuff and materials such condition was applicable only when it usedas singles dyestuff meanwhile when it as applied with other auxiliaries chotosan-formic was not complatibe for the rest of destuff and textilles material.